The Role of Proteomics in Identification of Key Proteins of Bacterial Cells with Focus on Probiotic Bacteria - Stastna, Miroslava (International journal of molecular sciences, 2024)
Probiotics can affect human health, keep the balance between beneficial and pathogenic bacteria, and their colonizing abilities enable the enhancement of the epithelial barrier, preventing the invasion of pathogens. Health benefits of probiotics were related to allergy, depression, eczema, cancer, obesity, inflammatory diseases, viral infections, and immune regulation. Probiotic bacterial cells contain various proteins that function as effector molecules, and explaining their roles in probiotic actions is a key to developing efficient and targeted treatments for various disorders. Systematic proteomic studies of probiotic proteins (probioproteomics) can provide information about the type of proteins involved, their expression levels, and the pathological changes. Advanced proteomic methods with mass spectrometry instrumentation and bioinformatics can point out potential candidates of next-generation probiotics that are regulated under pharmaceutical frameworks. In addition, the application of proteomics with other omics methods creates a powerful tool that can expand our understanding about diverse probiotic functionality. In this review, proteomic strategies for identification/quantitation of the proteins in probiotic bacteria were overviewed. The types of probiotic proteins investigated by proteomics were described, such as intracellular proteins, surface proteins, secreted proteins, and the proteins of extracellular vesicles. Examples of pathological conditions in which probiotic bacteria played crucial roles were discussed.
Keywords: bakteriální proteiny; proteomika; Probiotics; Bacteria; mass spectrometry-based proteomics; bacterial proteins; health-promoting effect; Proteomics; Animals; lidé; probiotics; Bacterial Proteins; Humans; zvířata; probiotika